2010
DOI: 10.1179/147683010x12611460764246
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fos immunoreactivity in the hypothalamus after glucose administration in pre- and post-weaning malnourished rats

Abstract: The present study explored the effects of malnutrition and nutritional rehabilitation on the response to glucose in hypothalamic nuclei involved in metabolic homeostasis. Male Wistar rats were malnourished during gestation-lactation (MGL) or at weaning to 55 days (MPW). Two groups of rats were rehabilitated with a balanced diet until 90 days (MGL-R and MPW-R, respectively). After a glucose tolerance test (GTT), brains were processed for Fos immunoreactivity (Fos-IR). Both malnourished groups displayed hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In agreement with our previous studies and with others, 6,7,18,19 we found that low-protein malnutrition during gestation and lactation as well as from weaning to P55 induced a long-lasting slowdown growth on the offspring. This leads to maintain low body weight of MGL-R and MPW-R rats until P90 in spite of a balanced diet nutritional rehabilitation.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In agreement with our previous studies and with others, 6,7,18,19 we found that low-protein malnutrition during gestation and lactation as well as from weaning to P55 induced a long-lasting slowdown growth on the offspring. This leads to maintain low body weight of MGL-R and MPW-R rats until P90 in spite of a balanced diet nutritional rehabilitation.…”
Section: Discussionsupporting
confidence: 95%
“…The 6% casein and the balanced diet have been previously employed by our group and others for similar studies. 7,15,16 Control and malnourished groups were obtained as described elsewhere. 6 Briefly, control (C) rats were born to dams nourished with a balanced diet during gestation and lactation and were maintained in the same nutritional condition until post-natal (P) day 90.…”
Section: Nutritional Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few report similar nutritional deficiency protocol as ours. 40) Further studies are needed to clarify the brain region responsible for the enhancement of the 5-HT 1A agonist induced head weaving reseponse in our postweaning PM model.…”
Section: Discussionmentioning
confidence: 99%